2016
DOI: 10.1111/cmi.12643
|View full text |Cite
|
Sign up to set email alerts
|

Threonine 80 phosphorylation of non-structural protein 1 regulates the replication of influenza A virus by reducing the binding affinity with RIG-I

Abstract: Influenza A virus evades host antiviral defense through hijacking innate immunity by its non-structural protein 1 (NS1). By using mass spectrometry, threonine 80 (T80) was identified as a novel phosphorylated residue in the NS1 of the influenza virus A/WSN/1933(H1N1). By generating recombinant influenza viruses encoding NS1 T80 mutants, the roles of this phosphorylation site were characterized during viral replication. The T80E (phosphomimetic) mutant attenuated virus replication, whereas the T80A (non-phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Conversely, phosphorylation of NS1 at Thr49 was recently identified as impairing the NS1-TRIM25 interaction, thereby suppressing its antagonistic activity of RIG-I signaling (102). Phosphorylation of another site on NS1, Thr80, has also been reported to disrupt NS1 binding affinity with RIG-I (103). Similar to IAV, the IBV non-structural NS protein (NS1-B) has recently been described as inhibiting RIG-I ubiquitination, which involves TRIM25-NS1 C-terminal effector domain interaction and the RIG-I/TRIM25/ NS1-B complex formation (104).…”
Section: Modulation Of the Ptmsmentioning
confidence: 99%
“…Conversely, phosphorylation of NS1 at Thr49 was recently identified as impairing the NS1-TRIM25 interaction, thereby suppressing its antagonistic activity of RIG-I signaling (102). Phosphorylation of another site on NS1, Thr80, has also been reported to disrupt NS1 binding affinity with RIG-I (103). Similar to IAV, the IBV non-structural NS protein (NS1-B) has recently been described as inhibiting RIG-I ubiquitination, which involves TRIM25-NS1 C-terminal effector domain interaction and the RIG-I/TRIM25/ NS1-B complex formation (104).…”
Section: Modulation Of the Ptmsmentioning
confidence: 99%
“…Phosphorylation of NP contributes to its nuclearcytoplasmic shuttling, self-oligomerization, and vRNP activity, thereby affecting viral growth (20)(21)(22)(23)(24). Phosphorylation of NS1 regulates its dimerization and nuclear localization (20), and phosphorylation of threonine at residues 49 and 80 of NS1 suppresses its interferon-antagonistic activity and binding affinity with RIG-I, respectively, leading to attenuation of virus replication (25,26). Phosphorylation of the nuclear export The recombinant viruses possessing wild-type CM2, CM2-S78A, CM2-S103A, or CM2-S78/103A were generated by reverse genetics as described in Materials and Methods and designated rWT, rS78A, rS103A, or rS78/103A, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was approved by the Safety Committee for Gene Recombination Experiments of Yamagata University (no. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies showed that phosphorylation may also occur at Thr49, which inhibits NS1's association to TRIM25 and decreases NS1 ability to interfere with the IFN cascade [58]. Another study showed that Thr80 phosphorylation reduces interaction with retinoic acid-inducible gene 1-like receptor dsRNA helicase enzyme (RIG-I) hence making NS1 unable to inhibit the IFN cascade [59]. Some H5N1 subtype strains display a mutation in Asp92 to Glu92 which reduces the strength of the hydrogen bonding interaction between Glu92 Ser195 and Thr197.…”
Section: Post-translational Modifications: Phosphorylation Sumoylatimentioning
confidence: 99%